Bcom ldan ʼdas Tshe-dpag-tu-med-pa lha dguʼi dkyil ʼkhor gyi cho ga ʼchi med grub paʼi lam bzaṅ źes bya ba bźugs so - Dkon-mchog-lhun-grub, Ṅor-chen, 1497-1557 (Sa-ṅor chos tshogs, 1968)
Buddhist liyutgical text of the Sakyapa sect outlining a method for the performance of the mandala of Amitayus, a ritual for obtaining longevity.